The Catholic imaginary and the cults of Elizabeth, 1558 - 1582 - Hamrick, Stephen (Ashgate, 2009)
The queen's court, the city, and Catholicism -- Barnabe Googe and Elizabeth's barbed horse -- The almoner and the queen -- Gascoigne's royal confessions -- Thomas Watson, the Earl of Oxford, and Queen Elizabeth